Comportamiento agronómico de dos variedades de Brócoli (Brassica oleracea ) sometidas a cuatro densidades de siembra en la parroquia “Chanduy”, provincia de Santa Elena - Torres Machado, Lhiry María (2016)
VIII. SUMMARY This research was conducted in the Canton Santa Elena, parish Chanduy, Commune "Pechiche" located at Km 2 via -San Rafael - Chanduy. The land is located at the geographic coordinates of 020 40 '/ s 020 20 "South Latitude and 810 0' / W 800 30" west longitude, north utm 0,539,264 9,743,856 and this, with a height of 39.5 meters, presents a dry tropical climate with average annual temperature of 25.2 ° C, an annual rainfall of 2500 mm and relative humidity of 58%. The floor is flat topography, clay loam and regulate drainage. The objectives were to identify the variety most suitable for planting in the province of Santa Elena Broccoli; determine the optimal seeding density culture to achieve greater production and economically analyze the treatments. two varieties of broccoli Heritage and Legacy, interaccionadas with densities of 50000, 55555, 62500 and 66666 (plants / ha), represented Factor A varieties of broccoli and Factor B planting densities were used. The experimental design used randomized complete block with eight treatments distributed in factorial arrangement A x B and three repetitions. For comparison of the averages of the variables Duncan test at 5% probability it was used. For the development of the research work seedbed preparation, soil analysis, soil preparation, transplanting, weeding, watering, fertilizing, phytosanitary control and harvesting took place. To estimate the effects of treatments you took the data rate of engraftment, plant height at 30, 60 and 90 days after transplantation, days to flowering and harvesting, stem diameter and pellets, crop yield and economic analysis. By the above results it was determined that the two varieties of broccoli (Heritage and Legacy) under four planting densities showed acceptable agronomic performance in the parish "Chanduy" province of Santa Elena; the Legacy variety with planting 66666 plants / ha reported excellent percentage of engraftment and plant height at 30, 60 and 90 days after transplantation; Legacy variety flourished and harvested early, unlike the variety Heritage; the larger diameter of the stems and the pellets were reached with the variety Legacy with densities of 62500 and 66666 plants / ha and the highest grain yield and net profit was achieved with the variety of broccoli Heritage density planting 50000 plants / ha with 13,236.8 kg / ha and $ 1255.19.